"Everybody Wants to Work with Me": Collaborative Labor in Hip Hop. Issue 3 (27th May 2019) - Carter, Daniel; Welsh, Tyler
Abstract: In this article, we consider the production of hip hop as a form of collaborative labor. Drawing on an analysis of 228 hip-hop groups, we find that collaboration among artists has increased since the 1980s. We contextualize this pattern in relation to business practices in the music industry as well as broader labor trends in the United States. Ultimately, we argue that hip-hop artists experience labor conditions that are comparable to those of other U.S. workers; further, we find that both groups of workers adopt similar ideologies, accepting personal risk and downplaying loyalty to groups and companies.